Study: Cultural Performance as a Factor Influencing the Selection of Information by the Media - Filanowski, Błażej (Methods of communication and media researches. Theoretical and analytical perspective, 2021)
The purpose of this chapter is to analyze the challenges in the practical use of the case study method faced by the researcher. The problem is discussed on the example of action informally entitled "Wolno fotografować" (It’s allowed to take photos) perform in 2006 in Lodz. In this case, particular attention was paid to the effectiveness of the performance, which initiated long-term cooperation between local institutional media and urban activists.